UMPASA DAN UMPAMA DALAM PROSESI ADAT PERNIKAHAN SUKU BATAK TOBA : KAJIAN ANTROPOLINGUISTIK - al H, Shabrina Amelia Mubiina; Purba, Rodearni; Solihati, Nani (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2024)
Abstract This research focuses on spoken language in traditional Toba wedding ceremonies, through umpama and umpasa. The main aim of this research is to identify the narrative and meaning of umpasa and umpama in Toba Batak marriages. This research uses a qualitative approach, by observing, analyzing the process, and interpreting umpasa and umpama at the Toba tribe's traditional wedding which has been chosen by the author. The results of the research show that the Toba Batak tribe's traditional wedding ceremonies advise using spoken language consisting of umpasa and umpama. For example, atang - lutung Tarida i Pangkona means authority. For example, there are more forms of proverbs than umpasa as poetic expressions. Both of these things have benefits even though the words are short but provide deep meaning. Keywords: Anthropolinguistics, Umpama, Umpasa